The essential need for radio frequency management in satellite communication development / Dasimah Zainal and Noor Hidayah Tauhid Ahmad - Zainal, Dasimah; Tauhid Ahmad, Noor Hidayah (2014)
Radio frequency spectrum is the factor that has primary importance for the activity in the satellite communication sector. Sufficient radio frequency spectrum is of important element for the activity and effective work in the satellite communication industry. Radio frequencies are a valuable and finite natural resource and the demands upon their use are increasing almost daily with every new digital technology that rolls out. Radio Frequency Interference continues to revolve the satellite communicationsindustry as owners/operators see an incremental unauthorized carriers, cross-polarization interference and some other issues with regard to errors. Management of the RF spectrum is a complicated policy issue, with various entities at the national and international level providing oversight and coordination. With growing numbers of space technology and applications being developed and used, RFI is a challenging task and responsibility in ensuring the sustainability of this scarce resources especially at the Geostationary orbit (GEO), which allocate huge numbers of communication satellites whether it’s state owned and commercially operated.